Alloying of platinum and molybdenum for transparent counter electrodes. A strategy of enhancing power output for bifacial dye-sensitized solar cells. Issue 64 (12th July 2015) - Zhang, Huihui; Tang, Qunwei; He, Benlin
<x xml:space="preserve">Abstract</x> Design of a cost-effective counter electrode with no sacrifice of photovoltaic performances and power output for a bifacial dye-sensitized solar cell is a persistent objective in photovoltaic power generation.